2005
DOI: 10.1200/jco.2005.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine Plus Carboplatin Versus Mitomycin, Ifosfamide, and Cisplatin in Patients With Stage IIIB or IV Non-Small-Cell Lung Cancer: A Phase III Randomized Study of the London Lung Cancer Group

Abstract: A B S T R A C T PurposeThis phase III randomized trial (ISRCTN 52253218) compared two chemotherapy regimens, gemcitabine plus carboplatin and mitomycin, ifosfamide, and cisplatin, in chemotherapynaive patients with advanced non-small-cell lung cancer (NSCLC). The regimens were compared with regard to effects on survival, response rates, toxicity, and quality of life. Patients and MethodsEligible patients had previously untreated stage IIIB or IV NSCLC suitable for cisplatin-based chemotherapy. Randomly assigne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
95
2
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(104 citation statements)
references
References 22 publications
4
95
2
3
Order By: Relevance
“…The overall compliance rate regarding completion of the HRQOL forms during the study period was 88%, which is equal or better than previous lung cancer studies using the EORTC questionnaire (Cardenal et al, 1999;Scagliotti et al, 2002;Gridelli et al, 2003a, b;Smit et al, 2003;Rudd et al, 2005;Sederholm et al, 2005;Plessen et al, 2006). However, the higher frequency of toxicity and interventions after GC therapy were not reflected in any HRQOL difference between the treatment arms.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The overall compliance rate regarding completion of the HRQOL forms during the study period was 88%, which is equal or better than previous lung cancer studies using the EORTC questionnaire (Cardenal et al, 1999;Scagliotti et al, 2002;Gridelli et al, 2003a, b;Smit et al, 2003;Rudd et al, 2005;Sederholm et al, 2005;Plessen et al, 2006). However, the higher frequency of toxicity and interventions after GC therapy were not reflected in any HRQOL difference between the treatment arms.…”
Section: Discussionmentioning
confidence: 53%
“…For vinorelbine/platinum combinations, recent phase III studies have yielded median survival data ranging from 6.5 to 11 months (Wozniak et al, 1998;Kelly et al, 2001;Scagliotti et al, 2002;Fossella et al, 2003;Gebbia et al, 2003;Georgoulias et al, 2005;Martoni et al, 2005;Tan et al, 2005;Plessen et al, 2006). In the gemcitabine/platinum metaanalysis (Le Chevalier et al, 2005), median survival in the gemcitabine group was 9 months, reflecting the mean value for a number of studies (Le Chevalier et al, 1994;Cardenal et al, 1999;Sandler et al, 2000;Scagliotti et al, 2002;Schiller et al, 2002;Alberola et al, 2003;Gebbia et al, 2003;Smit et al, 2003;Zatloukal et al, 2003;Martoni et al, 2005;Rudd et al, 2005;Sederholm et al, 2005). Our shorter median survival is possibly explained by the high proportion of patients with PS 2 (28%), which is the most powerful predictor of survival in NSCLC patients (Stanley, 1980).…”
Section: Discussionmentioning
confidence: 96%
“…Seventy eight (71%) were treated with first-line carboplatin and gemcitabine. This regimen was the most commonly used platinum doublet regimen locally and within the UK prior to published data favouring pemetrexed for nonsquamous histology [Scagliotti et al 2008;Rudd et al 2005]. For reasons of PS, clinician preference or comorbidity, a different regimen was substituted in 32 (29%) cases.…”
Section: Resultsmentioning
confidence: 99%
“…Sederholm et al of the Swedish Lung Cancer Group demonstrated that GC conferred a significant survival advantage compared with gemcitabine alone. 8 Other Phase III trials demonstrated that the GC regimen was tolerated better; conferred a survival advantage over the combination of mitomycin, ifosfamide, and cisplatin; 15 and resulted in a comparable survival advantage and less nausea and emesis compared with GC. 7 Based on a large body of Phase II data, including those from our study, 9 and Phase III data, the GV regimen apparently produces less hematologic and nonhematologic toxicity, when it is compared indirectly with more standard combinations.…”
Section: Discussionmentioning
confidence: 99%